Sarcopenia and health-related outcomes: an umbrella review of observational studies - Veronese, Nicola; Bauer, Jürgen M. (European geriatric medicine, 2019)
To investigate associations of sarcopenia with adverse health-related outcomes, through an umbrella review method.
Gesehen am 04.05.2020